[Group Overlooking Heimaey] - Streng, Evelyn Fiedler (1975)
Photograph of a group of people overlooking Heimaey. The group stands on lava rock to the right, black lava rock hills extending down and surrounding the town. The town of white buildings with red and green roofs sit closely clustered to the left. Large, flat, grass-covered mountains sit along the grey ocean visible to the right.